2019
DOI: 10.1097/aog.0000000000003512
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Opioid Use Postpartum

Abstract: Personal or nonessential information may be redacted at the editor's discretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…A recent quality improvement study, for example, reviewed approximately 570 charts showing that the group who utilized the multimodal approach was associated with a 75% reduction in in-hospital total morphine milligram equivalents without an increase in measured pain or length of hospital stay [6]. Similarly, Rogers et al recently evaluated the impact of multimodal order set on opioid consumption and pain control in a rather large cohort of patients after vaginal and cesarean deliveries [14]. They reported that opioid use decreased by 26% and 18% among women who delivered vaginally or by cesarean, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A recent quality improvement study, for example, reviewed approximately 570 charts showing that the group who utilized the multimodal approach was associated with a 75% reduction in in-hospital total morphine milligram equivalents without an increase in measured pain or length of hospital stay [6]. Similarly, Rogers et al recently evaluated the impact of multimodal order set on opioid consumption and pain control in a rather large cohort of patients after vaginal and cesarean deliveries [14]. They reported that opioid use decreased by 26% and 18% among women who delivered vaginally or by cesarean, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids were given as needed based on therapeutic postpartum activity goals. The intervention group demonstrated a decrease in opioid use (92% vs 79%; P < .01) and in the amount of morphine milligram equivalents (MME) used (107 MME vs 71 MME; P < .01) 20 …”
Section: Resultsmentioning
confidence: 99%
“…The intervention group demonstrated a decrease in opioid use (92% vs 79%; P < .01) and in the amount of morphine milligram equivalents (MME) used (107 MME vs 71 MME; P < .01). 20 The 4 studies evaluating an intervention that altered medication dosages or timing were all retrospective cohort This study also compared 2 hospitals that conducted the intervention with 2 hospitals that did not conduct the intervention. However, for the purpose of this systematic review, we are only examining changes that occurred at the intervention hospitals.…”
Section: Interventions To Reduce Postpartum Opioid Use During the Inp...mentioning
confidence: 99%
“…Although maximizing nonopioid medications may be a helpful strategy for patients with complex pain needs like those with OUD and chronic pain, being opioid naive is typically an inclusion criterion for studies. 6,7 Limitations of our study include a relatively small sample size and that it was conducted at a single site that has an opioid-sparing protocol in place. Still, this work generates important insights to guide future work to balance opioid stewardship and harm reduction with adequate pain control in these high-risk populations.…”
Section: Fundingmentioning
confidence: 99%